Adaptation of African swine fever virus to HEK293T cells. Issue 5 (27th July 2021) - Wang, Tao; Wang, Liang; Han, Yu; Pan, Li; Yang, Jing; Sun, Maowen; Zhou, Pingping; Sun, Yuan; Bi, Yuhai; Qiu, Hua‐Ji
Abstract: African swine fever (ASF), caused by African swine fever virus (ASFV), is a highly contagious disease with high morbidity and mortality in domestic pigs. Although adaptation of ASFV to Vero cells has been investigated, the phenotypic changes and the corresponding genomic variations during adaptation of ASFV to other cell lines remain unclear. To obtain a cell‐adapted ASFV strain, different cell lines were tested to determine whether they support ASFV infection. Interestingly, the ASFV wild‐type strain ASFV‐HLJ/18 can infect HEK293T cells and replicate at a low level. After continuous passaging, the adapted ASFV strain can replicate efficiently in both HEK293T and Vero cells. However, the adapted ASFV strain displayed reduced infectivity in primary porcine alveolar macrophages compared to the corresponding wild‐type strain. Furthermore, stepwise losses at the left variable end of the MGF genes and accumulative mutations were identified during passaging, indicating that the ASFV strain gradually adapted to HEK293T cells. Comparison of MGF deletions in other cell culture‐adapted ASFV strains revealed that the deletions of MGF300 (1L, 2R and 4L) and MGF360 genes (8L, 9L, 10L and 11L) play an important role for the adaptation of ASFV to HEK293T cells at the early stage. The biological functions of the deletions and mutants associated with ASFV infection in HEK293T cells and pigs warrant further study. Overall, our findings provide new targets to elucidate the molecular mechanism of adaptation of ASFV to cell lines.